Preparation method of carbon-coated Na3V2 (PO4) 2F3 sodium ion battery positive electrode material
By variable temperature regulation in the sol-gel method, the carbon clad layer is formed, which solves the problem of poor rate performance of Na3V2(PO4)2F3 positive electrode material, significantly improves the rate performance and cycle stability of the material, and meets the application needs of high-energy-density sodium ion batteries.
Patent Information
- Application Number
- CN202411934023.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing sol-gel method prepares Na3V2(PO4)2F3 positive electrode materials with poor rate performance, especially when charging and discharging at high rate, the capacity retention rate is low.
By temperature control in the sol-gel method, the degree of oxidation of vanadium elements is controlled, the internal conductivity of the material is improved, and a uniform carbon cladding layer is formed, which improves the rate performance and cycle stability of the material.
The first week of the material's Coulomb efficiency, cycle life and rate performance were significantly improved, especially the rate performance under fast charging and discharge conditions. The first week of the capacity reached 124.46mA/g, the capacity retention rate reached 77.24% after 1,000 cycles, and the capacity at 30C rate reached 103.58mA/g.
Smart Images

Figure CN119725474A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a positive electrode material for a sodium ion battery, and belongs to the technical field of material synthesis. Background Art
[0002] Sodium-ion batteries (SIBs) have attracted widespread attention due to their abundant sodium resources and electrochemical mechanisms similar to those of current mainstream lithium-ion batteries (LIBs). Among the positive electrode materials of sodium-ion batteries, Na3V2(PO4)2F3, as a compound with a NASICON structure, has attracted much attention due to its high conductivity and stable three-dimensional structure. However, there are still some key problems that restrict the practical application of this type of material: 1) The discharge capacity is too low, and the discharge capacity at a small rate is only about 110mAh / g, which is less competitive; 2) The rate performance is poor. Due to the low intrinsic electronic conductivity of the material, the capacity retention rate is low during high-rate charge and discharge. 3) Poor cycle stability: During long-cycle cycles, the material structure is unstable and the capacity decays severely. In the existing technology, the sol-gel method is an effective method for preparing Na3V2(PO4)2F3 positive electrode materials, but there is a bottleneck with limited rate performance improvement. Summary of the invention
[0003] The present invention aims to solve the technical problem of poor rate performance of Na3V2(PO4)2F3 positive electrode materials prepared by the existing sol-gel method, and provide a method for preparing carbon-coated Na3V2(PO4)2F3 positive electrode materials for sodium ion batteries. The present invention effectively improves the internal conductivity of the material by performing variable temperature control in the sol-gel method, significantly improves the first-week coulomb efficiency, cycle life and rate performance of the material, especially the rate performance under fast charge and discharge conditions. At the same time, the method of the present invention is simple in process and cost-controllable, and the prepared new positive electrode material can meet the application requirements of the next generation of high energy density sodium ion batteries.
[0004] The method for preparing the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material of the present invention is carried out according to the following steps:
[0005] 1. Weigh sodium salt, trivalent vanadium source, phosphate and fluoride salt according to the molar ratio of Na, V, P and F being 3:2:2:3, and then weigh the carbon source according to the molar ratio of C atoms in the carbon source to V atoms in the vanadium source being (0.75-0.85):1;
[0006] Alternatively, sodium salt, pentavalent vanadium source, phosphate and fluoride salt are weighed in a molar ratio of Na, V, P and F of 3:2:2:3, and then the carbon source is weighed in a molar ratio of C atoms in the carbon source to V atoms in the vanadium source of (0.75-0.85):1; and then the reducing agent is weighed, wherein the amount of the reducing agent added is just the amount of the pentavalent vanadium source V 5+ Completely restored to V 3+ The amount of
[0007] 2. Dissolve the carbon source or the carbon source and the reducing agent in water, adjust the pH value to 3.5-5.0, add the vanadium source to obtain a mixed solution; heat the mixed solution to 90-95°C, stir for 20-40 minutes, add the sodium salt, phosphate and fluoride salt, and continue stirring for 20-40 minutes;
[0008] 3. Lower the temperature of the mixed solution to 75-80°C and continue stirring until it becomes a wet gel;
[0009] 4. vacuum drying the wet gel at 75-80°C for 10-12h to obtain a dry gel;
[0010] 5. Grind the dry gel into powder, place it in a high-temperature furnace, heat it to 200-400°C in an inert atmosphere, pre-sinter it for 4-5 hours, and then heat it to 500-700°C for high-temperature sintering for 7-9 hours to obtain carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material.
[0011] Furthermore, the sodium salt described in step 1 is one of sodium metavanadate, sodium chloride, sodium fluoride, sodium hydroxide, sodium acetate, or a combination of several thereof.
[0012] Furthermore, the pentavalent vanadium source described in step one is one or a combination of two of ammonium metavanadate, sodium metavanadate, and vanadium pentoxide; the trivalent vanadium source described in step one is one or a combination of two of vanadium acetate, vanadium fluoride, vanadium phosphate, and vanadium trioxide.
[0013] Furthermore, the phosphate described in step 1 is one or a combination of diammonium phosphate, phosphoric acid and sodium phosphate.
[0014] Furthermore, the fluoride salt in step 1 is one or a combination of ammonium fluoride, sodium fluoride and vanadium fluoride.
[0015] Furthermore, the carbon source in step 1 is one or a combination of glucose, sucrose, ethylene glycol, polyethylene glycol (PEG), citric acid, and ascorbic acid;
[0016] Furthermore, the reducing agent in step 1 is one of ethylene glycol, citric acid, glucose, oxalic acid, ammonium carbamate, urea, ascorbic acid, sodium borohydride, or a combination of two thereof.
[0017] Furthermore, in step 2, the mass ratio of solute to water is 1:(15-30). The concentration of the solution affects the reaction time. If the concentration is too high, the V element will be partially oxidized, and if the concentration is too low, the reaction will not be sufficient to generate impurities.
[0018] Furthermore, the material used to adjust the pH value in step 2 is one or a combination of ammonia water and sodium hydroxide;
[0019] Furthermore, in step 2, the pH value is adjusted to 4.2-4.6.
[0020] Furthermore, the inert atmosphere in step 5 is nitrogen or argon. Inert gas can avoid oxidation and improve the uniformity of carbon coating.
[0021] The method for preparing the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material of the present invention greatly improves the high-rate performance and cycle performance of the material by adjusting the sol-gel temperature. The uniform carbon coating can provide a channel for the rapid transmission of sodium ions, thereby improving the rate performance of the material. Since the sol-gel method is carried out in an open dissolution system, there is more oxygen in the synthesis environment, and the high temperature is used for driving, the V element in the material is very easy to oxidize. In the preparation process of the material, ensuring that the trivalent V is not oxidized is the key to ensuring that the material capacity is fully released, because for the sodium vanadium fluorophosphate positive electrode material, its capacity is determined by V. 3+ / V 4+If there is an incompletely reduced V element in the reaction process, it will affect the capacity release, resulting in an initial capacity of only about 110 mAh / g. The performance of using a single temperature has its own advantages. Most of the traditional sol-gel temperatures use 80°C, but the performance at 80°C is average. The low-rate performance at 95°C is excellent, but the decay rate with the increase of the rate is much faster than that of the material prepared at a relatively low sol temperature. This is because the high-temperature sol-gel synthesis affects the quality of the carbon coating and the particle size of the material, resulting in a decrease in conductivity. Therefore, the rate performance decays faster under high current conditions, so the high-rate performance is not as good as the material prepared at 85°C. However, the lower the temperature, the better the rate performance, because the temperature will affect the time it takes for the sol-gel to complete. If the temperature is too low and the synthesis time is extended, the performance will decrease. Taking these elements into consideration, the idea of variable temperature operation is proposed. A higher early temperature can control the oxidation degree of the V element, and a lower temperature (75-80°C) is used in the later stage to improve the charge transfer dynamics, improve the capacity and cycle performance of the material at a large rate, and form a uniform and good carbon coating layer while synergistically controlling the material particle size, which can solve the disadvantage of low ionic conductivity of the sodium vanadium fluorophosphate material itself. Under the synergistic optimization of the two temperatures, the rate performance and cycle stability of the NVPF material are significantly improved, especially the problems of slow ion migration rate and unstable structure under large current charge and discharge, thereby improving the comprehensive performance of the battery. The carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared by the present invention has a first-week capacity of 124.46mA / g (1C rate), a capacity retention rate of 77.24% after 1000 cycles, and a capacity of 103.58mA / g at a 30C rate.
[0022] The carbon-coated Na3V2(PO4)2F3 sodium ion battery cathode material prepared by the method of the present invention is a new cathode material with excellent performance, simple process and controllable cost, which can meet the current application requirements of high-rate performance sodium ion batteries. The optimization method is simple and easy to implement, with low cost, and can be used for high energy density sodium ion batteries in the fields of low-speed vehicles, grid energy storage and emergency backup power supply. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD spectra of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4;
[0024] Figure 2 This is a SEM image of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1;
[0025] Figure 3A comparison chart of the first week charge and discharge curves of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4;
[0026] Figure 4 A comparison chart of the charge and discharge curves of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4 at a rate of 30C;
[0027] Figure 5 A comparison chart of the rate performance of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4;
[0028] Figure 6 This is a performance comparison chart of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4 after 1000 cycles at a 5C rate. DETAILED DESCRIPTION
[0029] The beneficial effects of the present invention are verified by the following examples.
[0030] Example 1: The preparation method of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material of this embodiment is carried out according to the following steps:
[0031] 1. Weigh 0.252 g of sodium fluoride, 0.364 g of vanadium pentoxide, and 0.46 g of ammonium dihydrogen phosphate, where the molar ratio of Na, V, P, and F is 3:2:2:3, and then use 0.6147 g of citric acid as a carbon source and reducing agent, and the molar ratio of citric acid to V atoms is 0.8:1;
[0032] 2. Dissolve citric acid in water, add ammonia water to adjust the pH value to 4.4, and then add vanadium pentoxide to obtain a mixed solution; raise the temperature of the mixed solution to 90°C and stir for 30 minutes, then add sodium fluoride and ammonium dihydrogen phosphate, and continue stirring for 30 minutes;
[0033] 3. Lower the temperature of the mixed solution to 80°C and continue stirring for 60 minutes to obtain a wet gel;
[0034] 4. Dry the wet gel in vacuum at 80°C for 12 h to obtain a dry gel;
[0035] 5. Grind the dry gel into powder, place it in a high-temperature furnace, heat it to 300°C in an inert atmosphere for pre-sintering for 4 hours, and then heat it to 600°C for high-temperature sintering for 8 hours to obtain carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material.
[0036] Comparative Example 1: The difference between this comparative example and Example 1 is that the temperature in step 2 and step 3 is both 80°C, and the other steps and parameters are the same as those in Example 1.
[0037] Comparative Example 2: This comparative example is different from Example 1 in that the temperature in step 2 and step 3 is both 85°C, and the other steps and parameters are the same as Example 1.
[0038] Comparative Example 3: This comparative example is different from Example 1 in that the temperature in step 2 and step 3 is both 90°C, and the other steps and parameters are the same as Example 1.
[0039] Comparative Example 4: The difference between this comparative example and Example 1 is that the temperature in step 2 and step 3 is both 95°C, and the other steps and parameters are the same as Example 1.
[0040] Example 1 is prepared by a variable temperature strategy, while Comparative Examples 1 to 4 are materials prepared by sol-gel at a conventional single temperature. The materials prepared in Example 1 and Comparative Examples 1 to 4 are subjected to X-ray diffraction (XRD) tests, and the obtained XRD patterns are as follows: Figure 1 As shown. Figure 1 It can be seen that the main diffraction peak positions of the sample prepared by the variable temperature strategy for sol-gel in Example 1 are basically consistent with those of the sample prepared by the conventional single temperature, indicating that the variable temperature strategy did not significantly change the crystal structure of the material. However, the peak intensity of the sample prepared by the variable temperature strategy is slightly enhanced, and the peak shape is sharper, while the peak position is slightly changed, closer to the standard spectrum, indicating that the structure has been optimized.
[0041] Figure 2 This is a scanning electron microscope photo of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1. Figure 2 It can be seen that the variable temperature strategy is used to prepare a nanoscale uniform block structure, and the small particle size ensures that the material has a large specific surface area and can fully contact with the electrolyte.
[0042] The materials prepared in Example 1 and Comparative Examples 1 to 4 were mixed with a conductive agent (super P) and a binder (PVDF) at a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added. The mixture was stirred for 4 hours to prepare a slurry, which was then coated on an aluminum foil. The coating thickness was controlled to be 200 μm, and the mixture was dried in a vacuum oven at 80°C for 12 hours. The mixture was cut into discs with a diameter of 10 mm and compacted to a thickness of about 60 μm to prepare an electrode. A pure metallic sodium sheet was used as a counter electrode, a glass fiber (GF-D) was used as a diaphragm, and 1 mol·L -1NaClO4 dimethyl carbonate (DMC), ethylene carbonate (EC) (volume ratio 1:1) and 5% fluoroethylene carbonate (FEC) organic solution were used as electrolytes, and assembled into CR2025 button cells in a glove box filled with high-purity Ar with water and oxygen content less than 1ppm, and assembled into 2032 button cells for testing. The test conditions are as follows:
[0043] (1) First week charge and discharge test: 1C (1C = 128.3mA / g);
[0044] (2) Cycle performance test: 5C, voltage range 2.0-4.5V;
[0045] (3) Rate performance test: 1C, 5C, 10C, 12C, 20C, 30C.
[0046] Figure 3 The first week charge and discharge curve comparison diagram of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4. As can be seen from the figure, the sample prepared by the variable temperature strategy in Example 1 has higher charge and discharge capacity than the sample prepared by a single temperature, reflecting that the material has a good structure that can meet the more sufficient embedding and de-embedding of sodium ions, and the platform in the high-voltage discharge range is longer, so the capacity of the material is increased.
[0047] Figure 4 The charge and discharge curves of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4 at a rate of 30C are compared. As can be seen from the figure, under the high-rate charge and discharge mode of 30C, the material prepared by the variable temperature strategy in Example 1 better maintains the platform in the high-voltage range, while the material prepared by a single temperature has a certain degree of attenuation in the high-voltage section, and at the same time, the performance loss of the material in the low-voltage discharge platform discharge interval is less, so the overall capacity is higher than that of the material prepared at a single temperature, indicating that the sample prepared by the variable temperature strategy has excellent electronic conductivity, and can also greatly guarantee the material performance under the condition of high-rate rapid charge and discharge.
[0048] Figure 5The figure shows the rate performance comparison of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4. As can be seen from the figure, under the condition of single temperature preparation, the material prepared at high temperature has a higher relative capacity, but the loss is large at a large rate, while the sample prepared at a relatively low temperature of 85°C has better performance under high rate conditions. After the variable temperature strategy is adopted in Example 1, the overall capacity is increased by 3-5mA / g compared with the single temperature. It not only combines all the advantages of the material prepared at a single temperature, but also can release a larger capacity on its basis. At a rate of 1C, the capacity is as high as 124.46mA / g, which is close to the theoretical capacity value of the material (128.8mA / g).
[0049] Figure 6 The performance comparison chart of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4 at 5C rate for 1000 cycles is shown. As can be seen from the figure, the material prepared by the variable temperature strategy in Example 1 not only has a higher discharge capacity, but also has the highest capacity retention rate during the cycle, indicating that the variable temperature strategy not only regulates the electronic conductivity of the material, but also optimizes the bulk structure of the material, making the material structure more stable and having better cycle performance.
[0050] The electrical performance data of the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 4 are shown in Table 1.
[0051] Table 1 Electrical properties of materials prepared in Example 1 and Comparative Examples 1 to 4
[0052]
[0053] from Figures 3 to 6 As can be seen from Table 1, the carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material prepared by sol-gel using a variable temperature strategy in Example 1 has a higher first-week capacity, better cycle stability and rate performance than the materials prepared by sol-gel at a conventional single temperature in Comparative Examples 1 to 4. By taking simple temperature control measures, not only the capacity of the material is improved, but also the structural degradation of the material during the cycle is effectively inhibited. In Example 1, the sol-gel was first performed at 90°C for 1 hour and then the temperature was adjusted to 80°C until it became a wet gel. The material performance reached the best, with a first-week capacity of 124.46mA / g (1C rate), a capacity retention rate of 77.24% after 1000 cycles, and a capacity of 103.58mA / g at a rate of 30C. Compared with the sample with the best rate performance at 85°C for sol-gel and the sample with the best performance at low rates at 95°C for sol-gel, the improved material has improved performance in all aspects.
[0054] The method of the present invention, based on the preparation by the sol-gel method, breaks through the temperature setting of the traditional sol-gel method through a temperature control, and improves the ion migration ability while controlling the vanadium element from being oxidized. The capacity, cycle stability and rate performance of the material are significantly improved. The modification method is simple and easy to operate, low in cost, and can be applied on a large scale. The sol-gel method using a variable temperature strategy provided by the present invention has the following advantages: (1) simple operation and easy large-scale production; (2) the process does not produce toxic gases and is environmentally friendly; (3) the improvement effect is significant, and multiple electrochemical performance indicators can be improved at the same time; (4) the scope of application is wide, and it can be extended to other types of sodium ion battery positive electrode materials. This simple and effective modification method provides a new idea for the development of high-performance sodium vanadium fluorophosphate positive electrode materials, and is expected to promote the industrial development of polyanion sodium ion batteries.
Claims
1. A method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material, characterized in that The method proceeds as follows:
1. Weigh sodium salt, trivalent vanadium source, phosphate and fluoride salt according to the molar ratio of Na, V, P and F being 3:2:2:3, and then weigh the carbon source according to the molar ratio of C atoms in the carbon source to V atoms in the vanadium source being (0.75-0.85):1; Alternatively, sodium salt, pentavalent vanadium source, phosphate and fluoride salt are weighed in a molar ratio of Na, V, P and F of 3:2:2:3, and then the carbon source is weighed in a molar ratio of C atoms in the carbon source to V atoms in the vanadium source of (0.75-0.85):1; and then the reducing agent is weighed, wherein the amount of the reducing agent added is just the amount of the pentavalent vanadium source V 5+ Completely restored to V 3+ The amount of 2. Dissolve the carbon source or the carbon source and the reducing agent in water, adjust the pH value to 3.5-5.0, add the vanadium source to obtain a mixed solution; heat the mixed solution to 90-95°C, stir for 20-40 minutes, add the sodium salt, phosphate and fluoride salt, and continue stirring for 20-40 minutes; 3. Lower the temperature of the mixed solution to 75-80°C and continue stirring until it becomes a wet gel; 4. vacuum drying the wet gel at 75-80°C for 10-12h to obtain a dry gel; 5. Grind the dry gel into powder, place it in a high-temperature furnace, heat it to 200-400°C in an inert atmosphere, pre-sinter it for 4-5 hours, and then heat it to 500-700°C for high-temperature sintering for 7-9 hours to obtain carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material.
2. The method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material according to claim 1, characterized in that: The sodium salt described in step 1 is one of sodium metavanadate, sodium chloride, sodium fluoride, sodium hydroxide, sodium acetate or a combination of several thereof.
3. A method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The pentavalent vanadium source described in step one is one or a combination of two of ammonium metavanadate, sodium metavanadate, and vanadium pentoxide; the trivalent vanadium source described in step one is one or a combination of two of vanadium acetate, vanadium fluoride, vanadium phosphate, and vanadium trioxide.
4. A method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The phosphate described in step 1 is one or a combination of diammonium phosphate, phosphoric acid and sodium phosphate.
5. The method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The fluoride salt described in step 1 is one or a combination of ammonium fluoride, sodium fluoride and vanadium fluoride.
6. A method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The carbon source described in step 1 is one or a combination of glucose, sucrose, ethylene glycol, polyethylene glycol, citric acid, and ascorbic acid.
7. A method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The reducing agent described in step 1 is one of ethylene glycol, citric acid, glucose, oxalic acid, ammonium carbamate, urea, ascorbic acid, sodium borohydride, or a combination of two thereof.
8. The method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: In step 2, the mass ratio of solute to water is 1:(15-30).
9. The method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The material used to adjust the pH value in step 2 is one or a combination of ammonia water and sodium hydroxide.
10. A method for preparing a carbon-coated Na3V2(PO4)2F3 sodium ion battery positive electrode material according to claim 1 or 2, characterized in that The inert atmosphere described in step 5 is nitrogen or argon.
Citation Information
Patent Citations
Preparation method for nickel cobalt lithium manganate LiNixConMn1-x-yO2 of anode material of lithium ion battery
CN102709568A
A preparing method of a sodium ion battery cathode material Na3V2(PO4)3 / C
CN105914352A
Carbon-doped sodium vanadium phosphate cathode material as well as preparation method and application thereof
CN107845796A
Preparation method of positive pole material Na1.1V3O7.9 of lithium ion battery
CN108264085A
Method for adjusting and controlling size of lanthanum titanate La2Ti2O7(LTO) powder
CN108314079A
Cited By
Preparation method of multi-element doped carbon coated Na3V1.94 (TM) 0.06 (PO4) 2F3 sodium ion battery positive electrode material
CN120473502A
Multi-doped carbon-coated na3v 1.94 (TM) 0.06 Method for preparing sodium-ion battery cathode material of (po4)2f3
CN120473502B
Vanadium sodium fluorophosphate positive electrode material as well as preparation method and application thereof
CN120664518A